Біохімічні показники крові мурчаків за атеросклерозу на фоні застосування препаратів рослинного походження «Кардіофіл» та «Фітохол» - Антоненко, Петро Павлович; Antonenko, Petro; Antonenko, P. P.; Antonenko, P.; Cуслова, Наталія Іванівна; Suslova, Natalіya; Suslova, N. I.; Suslova, N.; Suslova, Natalia; Шульженко, Наталія Миколаївна; Shulzhenko, Nataliya; Shulzhenko, N. M.; et al. (Харківська держ. зоовет. акад., 2019)
Встановлено за експериментального атеросклерозу у мурчаків збільшення вмісту у сироватці крові загального холестеролу, тригліцеридів, ліпопротеїнів високої та низької густини,у порівнянні з референтною нормою. Проте, у мурчаків дослідної групи, яким задавали препарати «Кардіофіл» та «Фітохол», рівень тригліцеридів, загального холестеролу та ліпопротеїнів низької густини був достовірно нижчим, відповідно на 1,05 ммоль/л (Р<0,001), 1,62 ммоль/л (Р<0,001) та 0,39 ммоль/л (Р<0,05), а рівень ліпопротеїнів високої густини – вищим на 0,16 ммоль/л, у порівнянні з контрольною групою, що свідчить про гіполіпідемічні та антисклеротичні властивості фітопрепаратів. Сердечно-сосудистые заболевания являются основной причиной заболеваемости и смертности в США и многих развивающихся странах. Атеросклероз, наиболее распространенная причина многих сердечно-сосудистых заболеваний, характеризуется отложением липидов и холестерина на внутренней оболочке кровеносных сосудов, что приводит к образованию бляшек и сужению просвета. Считается, что окисление ЛПНП играет главную роль в прогрессировании атеросклероза. Некоторые исследования показали, что антиоксиданты могут задерживать прогрессирование атеросклероза. В настоящее время широко применяются лечебно-профилактические средства растительного происхождения, которые влияют на организм комплексно, поскольку в их состав входят биологически активные вещества, макро- и микроэлементы, витамины. К таким лечебно-профилактическим средствам относятся препараты «Кардиофил» и «Фитохол». Цель работы – определение гиполипидэмической и антисклеротической активности препаратов «Кардиофил» и «Фитохол», их влияние на общее состояние морских свинок. Для проведения эксперимента были сформированы две группы (контрольная и опытная) лабораторных животных (морских свинок) средней массой тела 500 г, самцы, в возрасте 1 год, по 5 животных в каждой. Все животные находились в одинаковых условиях кормления и содержания. Перед началом эксперимента животных выдерживали на карантине, для опыта отбирали здоровых морских свинок, которые хорошо поедали корм и имели нормальную двигательную активность. Атеросклероз и гиперлипидэмию у животных контрольной и опытной групп моделировали путем введения 2 мл смеси холестерина из расчета 0,5 г/кг массы тела с жирами (свиной жир и предварительно подогретое подсолнечное масло) в соотношении 4:1, которую задавали морским свинкам опытной группы за 7 дней до начала эксперимента внутрь за 30 минут до кормления. Животным опытной группы задавали препараты «Кардиофил» в дозе 5 капель 3 раза в сутки и «Фитохол» в дозе одна капля с небольшим количеством воды один раз в сутки в течение 30 дней. За животными в течение всего периода эксперимента велось наблюдение с учетом общих клинико-физиологических показателей, отбирали кровь для определения биохимических показателей. Животных выводили из эксперимента под газовым наркозом путем декапитации на 30 день эксперимента после 12-14 часового голодания. Для определения биохимических показателей крови у морских свинок кровь брали из хвостовой вены в пробирки с распределительным гелем и активатором свертывания Vacusera объемом 5 мл. Исследование крови проводили с помощью полуавтоматического биохимического анализатора Stat Fax 1904+ с использованием наборов реагентов «СпайнЛаб» г. Харьков, (Украина). Установлено, что нарушения обмена липопротеидов при атеросклерозе проявлялось более выраженным увеличением массы тела морских свинок контрольной группы, что в свою очередь может приводить к повышению артериального давления, нарушению ритма сердечной мышцы, уменьшению толерантности к физическим нагрузкам. Так, масса тела морских свинок контрольной группы на 30 день эксперимента увеличилась на 2,8%, опытной группы – на 1,9%. В результате исследования выявлено у морских свинок обоих групп на фоне атеросклероза увеличение содержания в сыворотке крови общего холестерина, триглицеридов, липопротеинов высокой и низкой плотности по сравнению с референтной нормой. Однако, у морских свинок опытной группы, которым задавали препараты «Кардиофил» и «Фитохол», уровень триглицеридов, общего холестерина и липопротеинов низкой плотности был достоверно ниже, соответственно на 1,05 ммоль/л (Р<0,001), 1,62 ммоль/л (Р<0,001) и 0,39 ммоль/л (Р<0,05), а уровень липопротеинов высокой плотности – выше на 0,16 ммоль/л, по сравнению с контрольной группой. Таким образом, полученные данные свидетельствуют, что на возникновение и развитие атеросклероза у морских свинок могут влиять диеты, содержащие как высокое содержание жира, так и высокий уровень холестерина. Эффективность применения препаратов растительного происхождения «Кардиофил» и «Фитохол» при атеросклерозе у морских свинок указывает на их гиполипидемические и антисклеротические свойства. Cardiovascular disease is a major cause of morbidity and mortality in the United States and in many developing countries. Atherosclerosis is the most common cause of many cardiovascular diseases. It occurs by the deposition of lipids and cholesterol on the inner lining of the blood vessels, which leads to plaque formation and narrowing of the lumen. It is considered that oxidation of LDL plays a significant role in the progression of atherosclerosis. Certain studies have shown that antioxidants can delay the progression of atherosclerosis. Currently therapeutic and prophylactic herbal products are widely applied. These products affect the body comprehensively because it includes biologically active substances, macro and microelements, vitamins. “Cardiofil” and “Phytochol” are such therapeutic and prophylactic means. To determine the hypolipidemic, antisclerotic and overall impact of the “Cardiofil” and “Phytochol” to guinea pigs is the purpose of the work. Two groups (control and experimental) of 5 laboratory animals(guinea pigs) each one with an average body weight of 500 g and 1 year old were formed to carry out the experiment. All animals were kept and fed in the same way. The animals were quarantined before the experiment. Healthy guinea pigs, with good appetite and average locomotor activity were selected for the experiment. Atherosclerosis and hyperlipidemia in animals of the control and experimental groups were simulated by applications of 2 ml of a mixture that contains cholesterol and fats (lard oil and preheated sunflower oil in a ratio of 4: 1), at the cholesterol rate of 0.5 g / kg body weight, which was given to the guinea pigs for 7 days before the experiment began(every day, 30 minutes before feeding). The animals of the experimental group were given “Cardiofil” - 5 drops 3 times a day and “Phytochol” 1 drop with a small amount of water once a day for 30 days. Animals were monitored throughout the experiment, taking into account general clinical and physiological parameters. Blood was taken for examination of biochemical parameters. Animals were withdrawn from the experiment by decapitation under gas anesthesia on the 30th day of the experiment after a 12–14 hour starvation. Blood was taken from the tail vein into 5 ml tubes with a dispensing gel and a Vacusera coagulation activator to determine the biochemical parameters of blood in the guinea pigs. Blood tests were carried out using a “Stat Fax 1904+” semiautomatic biochemical analyzer using “SpineLab” reagent kits from Kharkiv, Ukraine. It was found that impaired lipoprotein metabolism for atherosclerosis was manifested by a more pronounced increase of the body weight of the control group, which in turn could lead to an increase in blood pressure, disturbances of the rhythm of the heart muscle, and a decrease of stamina. Thus, the body weight of animals of the control group on the 30th day of the experiment increased by 2.8% and by 1.9% of the experimental group animals. The study has revealed an increase of serum triglyceride content in the blood of control group animals by 1.3 times compared with the animals of the experimental group. The content of total cholesterol in the serum of the guinea pigs of the experimental group, which were given “Cardiofil” and “Phytochol” was lower by 1.8 times compared with the control group. Higher levels of HDL and LDL were found in serum of animals of the control group respectively 1.4 and 1.43 times compared with the animals of the experimental group. The atherogenic index is 1.2 times higher in the control group. Higher activity of AlAT, AsAT and creatine phosphokinase in serum of guinea pigs of the control group was found respectively in 1,2, 1,6 and 1,8 times compared with the experimental group animals. Increase of urea content by 1.06 times and decrease of total protein and creatinine content, respectively 1.1 and 0.9-fold in the serum of the control group guinea pigs, compared with the experimental group animals. The glucose content of the serum of the control group animals was 1.1-fold higher, compared to the experimental group guinea pigs. Thus, according to the obtained data, the beginning and development of atherosclerosis in guinea pigs may be influenced by diets containing both high fat and high cholesterol. The use of herbal preparations “Cardiophil” and “Fitochol” for atherosclerosis in guinea pigs exhibits their lipid-lowering and anti-sclerotic properties.
Биохимические показатели крови морских свинок при атеросклерозе на фоне применения препаратов растительного происхождения «Кардиофил» и «Фитохол»
Biochemical indicators of blood of guinea pigs with atherosclerosis against the background of application of herbal preparations “Cardiofil” and “Phytochol”
Антоненко Петро Павлович https://orcid.org/0000-0003-1469-0121 Cуслова Наталія Іванівна https://orcid.org/0000-0001-9500-9224 Шульженко Наталія Миколаївна https://orcid.org/0000-0002-8560-4350 Семьонов Олександр Володимирович https://orcid.org/0000-0002-8562-4108 Шкваря Микола Миколайович https://orcid.org/0000-0001-7279-3642
Keywords: ліпопротеїди високої та низької густини; high and low density lipoproteins; фітопрепарати; phytopreparations; гіполіпідемічні та антисклеротичні властивості; hypolipidemic and anti-sclerotic properties; тригліцериди; triglycerides; холестерол; cholesterol